Hubungan Antara Forward Head Posture Dengan Keseimbangan Pada Lanjut Usia - Alawiah, Susi; , Isnaini Herawati, SSt. FT, M. Sc; , Agus Widodo, S.Fis, M.Kes (2015)
Forward Head Posture (FHP) is a condition where the head extend out in front of the shoulder, in a normal posture the middle of the shoulder should align with the external auditory meatus. Age associated variability in the FHP, with older people demonstrating a more severe FHP. Balance deficits is a problem which found in older people. This research aim to know relationship between FHP with balance stability in older people. FHP was assessed via the craniovertebral angel (CVA) measured from a digitezed, lateral-view photograph of each subject. Balance stability was assessed using the Berg Balance Scale (BBS). This research done at Posyandu Lansia at Puskesmas Kawali on April-May 2015. This research method applied cross sectional observation approach with the total sample of 200 people and among those samples, 70 people had met the inclusion criteria. The data obtained are not normally distributed; statistical test was done by using Chi Square test. The results based on data analysis done by using Chi Square test showed that the value of p = 0.034, or the value of p <0.05 means Ho is rejected and Ha is accepted. It is concluded that there is a relationship between FHP with balance stability in older people. Hopefully this research can provide more information for the public.